Survival : global politics and strategy. Volume 66: Number 4: August-September 2024, Correlations of force - Allin, Dana; International Institute for Strategic Studies (Abingdon, Oxon ; New York, NY : Routledge, 2024)
Survival, the IISS's bimonthly journal, challenges conventional wisdom and brings fresh, often controversial, perspectives on strategic issues of the moment. In this issue: Douglas Barrie and Timothy Wright underscore the need for Washington to prioritise qualitative rather than quantitative improvements to its nuclear capabilities - free to read Catherine Fieschi examines the implications of an indecisive French election Daniel Byman and Seth G. Jones explore the increasing ties between China, Russia, Iran and North Korea and obstacles to deeper cooperation Veronica Anghel and Erik Jones examine how the European Union can utilise its most powerful instrument - enlargement - to stabilise its peripheries And eight more thought-provoking pieces, as well as our regular Book Reviews and Noteworthy column. Editor: Dr Dana Allin Managing Editor: Jonathan Stevenson Associate Editor: Carolyn West Editorial Assistant: Conor Hodges
Keywords: Strategy; Military policy; Disarmament; HISTORY / Military / Strategy